Escape of ionizing radiation from high-redshift dwarf galaxies: role of AGN feedback. Issue 4 (28th May 2018) - Trebitsch, Maxime; Volonteri, Marta; Dubois, Yohan; Madau, Piero
ABSTRACT: While low-mass, star-forming galaxies are often considered as the primary driver of reionization, their actual contribution to the cosmic ultraviolet background is still uncertain, mostly because the escape fraction of ionizing photons is only poorly constrained. Theoretical studies have shown that efficient supernova feedback is a necessary condition to create paths through which ionizing radiation can escape into the intergalactic medium. We investigate the possibility that accreting supermassive black holes in early dwarf galaxies may provide additional feedback and enhance the leakage of ionizing radiation. We use a series of high-resolution cosmological radiation hydrodynamics simulations where we isolate the different sources of feedback. We find that supernova feedback prevents the growth of the black hole, thus quenching its associated feedback. Even in cases where the black hole can grow, the structure of the interstellar medium is strongly dominated by supernova feedback. We conclude that, in the dwarf galaxy regime, supermassive black holes do not appear to play a significant role in enhancing the escape fraction and in contributing to the early ultraviolet background.